High‐sensitivity simultaneous quantification of tacrolimus and 13‐O‐demethyl tacrolimus in human whole blood using ultra‐performance liquid chromatography coupled to tandem mass spectrometry. (6th June 2019) - Ono, Hiroyuki; Suzuki, Yosuke; Kaneko, Tetsuya; Tanaka, Ryota; Sato, Fuminori; Sato, Yuhki; Mimata, Hiromitsu; Itoh, Hiroki
Abstract: Blood concentrations of tacrolimus show large variability among patients and the narrow therapeutic range is related to adverse effects. Therefore, therapeutic drug monitoring is needed for strict management. 13‐ O ‐Demethyl tacrolimus (13‐ O ‐DMT) was reported as the major metabolite formed by cytochrome P450 (CYP)3A such as CYP3A5. In previous studies, the best lower limit of quantification (LLOQ) was 0.1 ng/mL for both substances. However, this LLOQ may not be low enough now because the dosage of tacrolimus has decreased in recent years. The purpose of this study was to develop and validate a high‐sensitivity and high‐throughput assay for simultaneous quantification of tacrolimus and 13‐ O ‐DMT in human whole blood using ultra‐performance liquid chromatography with tandem mass spectrometry (UPLC–MS/MS). Thirty‐five stable kidney transplant recipients receiving tacrolimus were recruited in this study. The calibration curve range was 0.04–40 ng/mL. All calibration samples and quality control samples fulfilled the requirements of the US Food and Drug Administration and the European Medicines Agency guidelines for assay validation. Trough concentrations of tacrolimus and 13‐ O ‐DMT in 35 stable kidney transplant recipients receiving tacrolimus were within the range of the respective calibration curve. Our novel UPLC–MS/MS method is more sensitive than previous methods for quantification of tacrolimus and 13‐ O ‐DMT.